2017
DOI: 10.5348/ijhpd-2017-69-oa-5
|View full text |Cite
|
Sign up to set email alerts
|

Complications of acute pancreatitis in tertiary care hospital

Abstract: Aims: The aim of this study was to determine the complications of acute pancreatitis in tertiary care hospital. Methods: Hundred patients diagnosed with acute pancreatitis were analyzed in this prospective cohort study from July 2015 to July 2016. Complications were studied. Cholelithiasis was found to be the most common cause of acute pancreatitis in our setting. Results: Acute pancreatitis is defined as reversible inflammation of pancreatic parenchyma which is characterized by the presence of interstitial ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
2
1
Order By: Relevance
“…The results of the present study disagree with (Akhter et al, 2017) [1] who stated that, acute fluid collection around pancreas being the top line complication, followed by other complications including pleural effusion, pseudocyst, pancreatic ascites, sterile and infected pancreatic necrosis, portal or splenic vein thrombosis, hyperglycemia, hypocalcemia, and renal failure are rare. The results of the present study disagree with (Zerem, 2014) [16] who stated that, the most common local complication was acute fluid collection followed by pancreatic necrosis, pancreatic abscess and infected pancreatic necrosis, in the same line The results of the present study disagree with (Desai et al, 2016) [4] who stated that, the most common complications were pulmonary followed by acute renal failure.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of the present study disagree with (Akhter et al, 2017) [1] who stated that, acute fluid collection around pancreas being the top line complication, followed by other complications including pleural effusion, pseudocyst, pancreatic ascites, sterile and infected pancreatic necrosis, portal or splenic vein thrombosis, hyperglycemia, hypocalcemia, and renal failure are rare. The results of the present study disagree with (Zerem, 2014) [16] who stated that, the most common local complication was acute fluid collection followed by pancreatic necrosis, pancreatic abscess and infected pancreatic necrosis, in the same line The results of the present study disagree with (Desai et al, 2016) [4] who stated that, the most common complications were pulmonary followed by acute renal failure.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the present study agree with (Guercioni et al 2009) [5] who stated that, Women are two times more commonly affected, likely related to the increased prevalence of cholelithiasis in females. These result are in line with the result reported by (Akhter et al 2017) [1] who found that a female to male predominance with the ratio of www.nursingjournal.net 2:1. This epidemiological data was also confirmed in other study which stated that biliary acute pancreatitis being twice frequent in women than in men.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, we have observed that among pancreatic complications, acute fluid collection was the most common complication seen in 26.7% (16/60) patients. This is comparable to the studies done by Ramu et al [ 5 ] and Akhter et al [ 14 ], where acute fluid collection was the most common pancreatic complication (29.1% and 41% respectively) reported by both studies.…”
Section: Discussionsupporting
confidence: 90%
“…From Pakistan; AKI as complication of AP has been variably reported 1-14%, while mortality with AP ranges from 0 to 30%. 15 - 18 Present study is based on data from a tertiary renal care hospital therefore; prevalence of AP or AKI with AP cannot be commented as AP was treated by internists and surgeons according to etiology and only referred here when renal dysfunction is noticed. Tran DD et al report 16% prevalence of AKI with AP 19 , same authors have reported better prognosis in nonoliguric form of renal failure in their AP patients, but in our study 83% patients were oliguric on presentation with closely falling frequency among patients who recovered and died during acute illness.…”
Section: Discussionmentioning
confidence: 99%